2023
DOI: 10.1021/acs.macromol.2c01767
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolothiazole-Containing Conjugated Polymer with Electrochromism and Electrofluorochromism-Based Dual Performance for a Flip-Flop Molecular Logic Gate

Abstract: Dual-performance devices based on electrochromism and electrofluorochromism have recently gained much attention in display technology. However, getting electrochromism and electrofluorochromism from the same material is very challenging. Herein, we have synthesized a low-band-gap donor− acceptor conjugated thiazolothiazole-containing organic polymer, P-TzTz, that exhibited a quasi-reversible single-electron reduction to demonstrate a pale yellow-to-black (NIR region) electrochromism and a red-to-quenched elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The coloration efficiency (η CE ) can better describe the performance of optical density (ΔOD) with injected electrons ( Q ) . The η CE can be derived from the slope of the optical density change vs injected electron plot according to eq η normalC normalE = normalΔ O D Q = log ( T b T c ) Q …”
Section: Resultsmentioning
confidence: 99%
“…The coloration efficiency (η CE ) can better describe the performance of optical density (ΔOD) with injected electrons ( Q ) . The η CE can be derived from the slope of the optical density change vs injected electron plot according to eq η normalC normalE = normalΔ O D Q = log ( T b T c ) Q …”
Section: Resultsmentioning
confidence: 99%
“…Then, all TPA cores are oxidized to TPA •+ at 1.6 V vs Ag/Ag + . So, the absorption generated at 900 nm at 1.6 V is caused by the bipolaron formation in the polymer backbone, 50,64 which resulted in a strong chromic transition from yellow to green and significant decay in transmittance, as shown in the photograph (Figure 4b). The film generated the original color once the voltage is reversed to the normal state.…”
Section: Electrochromic Study Of Polyznmentioning
confidence: 99%
“…47 Most recently, Halder et al reported a thiazolothiazole-based conjugated polymer as an effective candidate with EC/EFC characteristics. 50 Corrente et al also reported benzothiadiazole-arylamine mixed-valence compounds exhibiting EC/EFC dual functions. 51 However, our group is interested in metallo-supramolecular polymers (MSPs), as they are considered an advanced class of materials for modern device technology.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The switching time T b 0.9 and T c 0.9 , which was defined as the time to switch between two different color states after voltage, switching reached 90% of the complete absorbance change and was determined using absorbance change plots (Figure 6). All of these polymers showed relatively acceptable switching times (below 9 s), and their bleaching times Tb 0.9 were all shorter than the coloring times Tc 0.9 , which is a common phenomenon even though there were existing counterexamples in some compound systems [24,25]. This indicates that the charge injection process was slower than extraction, which could be attributed to the congregation of the polymer film surface, which increased the potential barrier of oxidation and led to a slower dynamic process, where the path of charge extraction was faster with fewer obstacles than injection.…”
Section: Electrochromic Propertiesmentioning
confidence: 99%